Young adults and the digital public sphere: a cross-cultural perspective - Frenette, Micheline (2013)
This paper deals with the engagement of young adults in the digital public sphere and attempts to identify some important issues related to the phenomenon as well as some of the challenges for future research. It has often been asserted that the newer generations are disenchanted with traditional party politics and prefer alternative forms of political engagement. Concurrently, it has been stated that, because of their pervasive involvement with ICTs and the unique opportunities they offer, the digital public sphere has become a place of choice for them to enact these newer forms of political engagement. The hypothesis that young adults are part of a digital generation that has redefined its modes of functioning within society has been a motivating factor for a study conducted among university students in four different countries1 to see how these new practices play out in the various spheres of their lives. Among other issues, we explore to what extent and in what ways the Internet has become a new vector for political participation among young adults. We will use part of these data to support our reflection on young adults’ involvement in the digital public sphere and to re-examine the classical premises of what constitutes the public sphere. We conclude by sharing our insights on this phenomenon and discussing further avenues for research in this area.